La valoración de los activos biológicos y su incidencia en el patrimonio de la empresa - Honores Correa, Yajaira Tatiana (2015)
The correct valuation of the inventories do that the financial states in these type of organizations have main interest by part of the users, due to present of reasonable form the situation of the company at a given moment; fundamental base to take corrective, mainly above investment and financing of the productive active. The present job to deal with the thematic of the valuation of the shrimps in Machala city, well known for its contribution to the National production of products with exporting trajectory, and that it has become in a problematic to the accountant and other involved people with the effective valuation of the categories. This situation has carried, that in some cases; the countable system, not agree with the true piece of information that exist in the production. In the relevant part, it`s said opinions of some authors in reference to raised theme that it`s joined with the process to the value of the sources, managing to among the theoric and the practical. In the proposal is said some topics about the correct use and valuation of the possessions, to guarantee an efficient administration and that it directed to cover the organizational requirements.